Impact of random variations of air hole diameters and random variations of the centers position of air holes on operation parameters of a solid core microstructured optical fiber - Donskov, A. N.; Filipenko, A. I. (Вісник Харківського національного університету імені В. Н. Каразіна, 2011)
We investigated the impact of random variations of air hole diameter and random variations of the centers position of air holes on operation parameters in the case of solid core microstructured optical fiber with a ring of air holes. The found results show that at any of considered defect types mode field will have two pronounced maximums. At practical use an investigated type of the MOF special angular positioning end faces of fibers is necessary. We also have shown that random variations of inclusions diameter can increase total mode field power. In our research we used finite-element method.
Keywords: finite-element method; microstructured optical fiber; Gaussian distribution